Imposter Phenomenon in Pediatric Residency: An Empirical Simulation-Based Educational Study - Bahadır M. Samur; Furkan Maraşlı; İsmail Dursun (AVES Yayincilik, 2024)
Objective: The imposter phenomenon (IP) may have a negative impact on the ability of healthcare providers to make difficult and accurate decisions. This study presents an empirical approach, segregating the real imposters based on a simulation, and aims to investigate the prevalence and severity of IP and evaluate the attitude in the decision-making process of pediatric residents with impostorism. Materials and Methods: A simulation-based case study with the 113 pediatric residents was performed with the Clance Imposter Phenomenon Scale to identify IP scores and appropriate management skills for the case. The collected data were divided and combined into different categories based on the IP scale scores and the success of case management to further detect how real imposters were affected. Results: Our study revealed that 24 (21.2%) of residents have moderate, 33 (25.7%) of residents have frequent, and 29 (29.2%) of residents have intense impostorism feelings. The imposter scores were found to be higher among female participants (P = .006). However, when considering the prevalence of significant impostorism (defined as both frequent and intense), there was no statistically significant difference between females and males (P = .088). The data indicated that an increase in IP scores was associated with a higher likelihood of delayed pressing the help button for both the overall and post-exclusion groups (P < .001). The analysis also revealed a significant correlation and a monotonic-linear trend between IP scores and the decision-making process, even after excluding the unsuccessful participants (P < .001). Conclusion: This is the first study to demonstrate the prevalence of IP among pediatric residents, potentially leading to challenges in patient care and resulting in delayed decisionmaking and self-doubt with feelings of inadequacy. The findings support the claim that higher imposter scores are associated with a greater tendency to seek help from more experienced individuals, even when fully capable of managing cases independently. This emphasizes the importance of awareness about the IP, as these factors can directly impact both the well-being of trainees and patient care outcomes.